Fundamentals of managerial economics - Hirschey, Mark
The Eighth Edition of this market-leading text continues its tradition of providing a solid foundation of economic understanding for use in managerial decision making. It offers a practical treatment of economic theory and analysis in an intuitive, algebra-based format. Its focus is on presenting those aspects of economic theory and analysis that are most relevant to students of business administration, and a wide variety of examples and simple numerical problems are used to illustrate the application of managerial economics to a vast assortment of practical situations. The nature of the decision process and the role economic analysis plays in that process are emphasized throughout. This revision is designed to maximize accessibility for a student audience with little or no background in economics or higher-level mathematics. The text focuses on the economics--not the mathematics--of the managerial decision process